Die Süditalienische Stadt - Sabelberg, Elmar (ERDKUNDE, 1985)
The following paper shows that the South-Italian city must be considered as a separate regional city-type. The model, developed here (Fig.1), explains the characteristic functional areas and their dynamics: 1. In the historic city-core the majority of the houses are former one-room row-houses of low class groups, which are enlarged by the building up of new flats. By permanent housing extensio a street-pattern with many blind alleys has developed (Fig. 3). 2. In the same area multi-storey owner occupied apartment houses are irregularly distributed. 3. The palazzo streets as residential areas of the former upper class before 1800 differ from the other buildings. Today, these palazzi are inhabited by low class groups. 4. The Corso street, laid out in the historic city-core as a residential area and commercial center of the upper class during the 19th century, has to a certain degreee retained its function as part of the modern commercial centre (Fig. 4). 5. The central market area is a separate functional area offering all kinds of low quality commodities as a daily market (Fig. 5). 6. In the newly built-up areas recent shopping streets with more specialized high value goods and additional service functions located in luxurious apartment-buildings grow up (Fig. 6). These streets are also part of the commercial centre and residential areas of today's upper class (Fig. 7). The model also explains the dynamics of the South-Italian city: 1. The residential area of the upper class and the high order commercial centre have been shifted several times since 1800. 2. Some of the basic structural elements of the city are scale-dependent; they modify with the city size. 3. Essential differences exist between the South-Italian and the Anglo-Saxon type of city. A CBD as described for western European cities does not exist. Furthermore, there is no hierarchy of shopping-centres. The commercial areas of high order tertiary uses are also high status residential areas. The effects of social segregation have created a spatial pattern rather different from the Anglo-Saxon model. On the basic of these variations a separate South-Italian city must be distinguished.